Retrospective study of massive obstetric haemorrhage and its materno fetal outcomes in a tertiary care centre - Padmasekar, Anju; Jothy, Shyamala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Massive obstetric haemorrhage is defined as blood loss of >1500 ml, or a decrease in haemoglobin>4 gm/dl or acute transfusion requirement of >4 units of blood when need for further transfusion is foreseeable. The purpose of this study is to analyse the demographic, medical and obstetric risk factors for massive obstetric haemorrhage and it’s materno fetal outcomes. Methods: Criteria for patient selection was all patients who had an acute obstetric haemorrhage necessitating a transfusion of >4 units of blood at a stretch when there was a need for more. This is a retrospective study conducted for a period of one year January to December 2015. Data regarding all cases under study during this period was obtained from Medical Records Department with prior permission. This study was conducted in the Department of Obstetrics and Gynecology, Government Raja Mirasudhar Teaching Hospital, Thanjavur Medical College, Tamil Nadu. Maternal outcomes like mode of delivery, rate of hysterectomy, postpartum complications, maternal mortality and fetal outcomes like intra uterine death, still birth and preterm birth were analysed. Results: The rate of massive obstetric haemorrhage in our hospital during the study period was 5.7/1000 births. Massive obstetric haemorrhage contributed to 25% of all maternal deaths in 2015. Atonic PPH was the commonest cause. Multiparity and previous caesarean section were identified to be significant risk factors. Conclusions: We found an increased association of massive obstetric haemorrhage with multiparity, caesarean sections and pre-eclampsia. Atonic PPH was the commonest cause. Massive obstetric haemorrhage had contributed significantly to adverse maternal and perinatal outcomes.